2018
DOI: 10.1370/afm.2280
|View full text |Cite
|
Sign up to set email alerts
|

Revitalizing Generalist Practice: The Montreal Statement

Abstract: "Today, the need for people-centered primary health care is greater than at any time in history" 1The challenges facing our health systems are immense. International efforts strive to meet the needs of aging populations, the rising prevalence of chronic disease and illness, and the changing impact of complex social factors (including health care) on individuals' experiences of, and capacity to manage, illness. The international community has pledged to renew its efforts to better align health care to a person-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…The primary components of EGP are 'person-centred decision-making' and 'interpretive medical practice', 6 and as confirmed in the present study, family medicine experts in Japan also viewed these elements as critical to their practice, acknowledging that this is the core expertise of generalist care. 8 In addition, Japanese family doctors cited care integration and effective use of healthcare resources as positive impacts of EGP, consistent with earlier findings. 7 Reeve et al 7 identified 'lack of a consistent understanding of distinct expertise', 'competing priority inhibiting EGP', 'lack of consistent development of skills in interpretive practice', and 'lack of resources for manageable monitoring building'.…”
Section: Comparison With Existing Literaturesupporting
confidence: 84%
See 1 more Smart Citation
“…The primary components of EGP are 'person-centred decision-making' and 'interpretive medical practice', 6 and as confirmed in the present study, family medicine experts in Japan also viewed these elements as critical to their practice, acknowledging that this is the core expertise of generalist care. 8 In addition, Japanese family doctors cited care integration and effective use of healthcare resources as positive impacts of EGP, consistent with earlier findings. 7 Reeve et al 7 identified 'lack of a consistent understanding of distinct expertise', 'competing priority inhibiting EGP', 'lack of consistent development of skills in interpretive practice', and 'lack of resources for manageable monitoring building'.…”
Section: Comparison With Existing Literaturesupporting
confidence: 84%
“…[5][6][7] Whole-person, individually-tailored clinical decision-making is seen as the defining expertise of generalist care internationally. 8 Such expertise should be fostered through formal training, not merely experiential learning. 5 In Japan, like many other countries, generalist care is seen as increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…The central goal of this transformation is to produce excellent community-focused personal physicians, 50 broadly-educated expert generalists 51 who establish and sustain ongoing, trusting relationships with patients over time and across place. As clinically-competent, trusted partners and advisors who understand patients' goals and life circumstances, personal physicians provide, or work with others to provide, health care services that patients want and need.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of this review include its broad search and use of a mixed-methods approach to include all relevant empirical study designs to produce insights greater than reported with quantitative and qualitative findings that are separated. 11 , 22 , 29 31 Studies from all countries are eligible for inclusion and the international team includes learners, researchers, and clinicians, which will promote critical discussions on the interpretations. A limitation of this protocol is that the team is composed of physicians and researchers based in general practice.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Yet recruitment into generalist specialties in many developed countries, including the US, UK and Canada is less than anticipated to meet societal health care needs. [5][6][7] Professional bodies have repeatedly endorsed training in generalism across the specialties 2,[8][9][10][11] and equipping graduates with a generalist skill-base is a key target outcome at an undergraduate level. 12,13 Health systems have also established targets and programmes to attempt to increase the number of generalist-trained doctors, such as the NHS Long Term Plan in the UK, 14 which emphasises both the need to develop generalist skills as well as specifically aiming for more general practitioners (GPs).…”
Section: Introduction Background and Rationalementioning
confidence: 99%